The Influence of E-Commerce and Entrepreneurship Knowledge through Self-Efficacy on Interest in Entrepreneurship in Students Majoring in Online Business and Marketing at State Vocational High School 1 Jombang: Pengaruh E-Commerce dan Pengetahuan Kewirausahaan melalui Self Efficacy terhadap Minat Berwirausaha pada Siswa Jurusan Bisnis Daring dan Pemasaran SMK N 1 Jombang - Muhammad Alvin Haidar; Finisica Dwijayanti Patrikha (Journal of Multidisciplinary Science, 2024)
This research was conducted to determine the effect of e-commerce, entrepreneurial knowledge through self-efficacy on the interest in entrepreneurship of students majoring in Online Business and Marketing at SMKN 1 Jombang. The sample in this study were 106 students. The results of this study explain that partially 1) There is an influence of e-commerce on interest in entrepreneurship, 2) There is a positive influence of entrepreneurial knowledge on interest in entrepreneurship, 3) There is a positive effect of self-efficacy on interest in entrepreneurship, 4) There is a positive influence of e-commerce on self efficacy, 5) There is a positive influence of entrepreneurial knowledge on self-efficacy, 6) There is a positive effect of e-commerce through self-efficacy as a moderating variable on interest in entrepreneurship, 7) There is a positive influence on entrepreneurial knowledge through self-efficacy as a moderating variable on interest in entrepreneurship